A single-chip integrated spectrometer via tunable microring resonator array - Zheng, Shaonan (2021)
We experimentally demonstrate a spectrometer, which consists of an arrayed waveguide grating (AWG), tunable microring resonator (MRR) array, and waveguide-coupled Ge-on-Si photodetector, all integrated onto a single chip. The spectrometer achieves high resolution (0.1 ± 0.029 nm) and large bandwidth (25.4 nm) in 9 channels with a small footprint of 3 × 3 mm2. It has high potential to enable a high-performance spectrometer for applications such as environmental monitoring, spectroscopy, biological and chemical sensing, etc.